Disseminated Coccidioidomycosis Complicated by Vasculitis: A Cause of Fatal Subarachnoid Hemorrhage in Two Cases - Erly, William K.; Labadie, Enrique; Williams, Paul L.; Lee, Darlene M.; Carmody, Raymond F.; Seeger, Joachim F. (American Journal of Neuroradiology, 1999)
Summary: We describe two cases of disseminated coccidioidomycosis that were complicated by fatal subarachnoid hemorrhage. In the first case, a left middle cerebral artery aneurysm and long-segment vasculitis occurred. In the second case, MR imaging revealed an enlarging coccidioidal granuloma at the tip of the basilar artery, and the artery subsequently ruptured. Fatal intracranial hemorrhage is a rare complication of disseminated coccidioidomycosis.